Bones Will Crow : An Anthology of Burmese Poetry - Byrne, James, 1977-; Ko ko Thett 1972- (Book collections on Project MUSE., 2013)
"This is the first anthology of contemporary Burmese poets published in the United States. It includes the work of Burmese poets who have been in exile and in prison. It will announce to American readers the vitality and importance of Burmese poetry to world literature"